STUDI DESKRIPTIF PENGELOLAAN PEMBELAJARAN TEMATIK DALAM MENGEMBANGKAN SIKAP SPIRITUAL DI KELAS III B SD N 09 KOTA BENGKULU - Ihwana, Ety; Juarsa, Osa; Agusdianita, Neza (Jurnal PGSD, 2017)
This  study  aimed  to  describe  the  management  of  thematic  learning  in  developing spiritual attitudes related to learning design, implementation and evaluation of learning spiritual  attitude  in  class  III  B  Elementary school  number  09  Bengkulu  City.  The method in this research is descriptive qualitative data collection techniques such as observation, interviews, and documentation. Data analysis was performed by means of data reduction, data display, and verification. Furthermore, to test the validity of the data used extension of observation, improve endurance, triangulation techniques, and check.  In  this  study concluded that  1) Design  /  thematic lesson  planning done by teachers using the syllabus and lesson plans. 2) Implementation of learning is already visible management spiritual attitude. Preliminary activities through reading prayers. Core activities through the implementation of learning that teachers can use to associate the material in accordance with the management of spiritual attitudes, and activities such as closing prayer after completion of learning. 3) Evaluation of management of spiritual attitudes of teachers conducted in a way to make observations on the spiritual attitude of students daily from early learning to finish. Evaluation of teachers carried out using observation without special note.